MAKNA TERSEMBUNYI KOMUNIKASI NONVERBAL DALAM FILM IRONY MOTHER EARTH CALLING - Gavrila Joanita Juliana Tarumingi; Pierre Mauritz Sundah (Universitas Pelita Harapan, 2026)
This study aims to analyze the hidden meanings conveyed through nonverbal communication in the short film Irony Mother Earth Calling directed by Daffa Izzudin, using Roland Barthes’ semiotic approach. The research focuses on identifying and interpreting Barthes’ five semiotic codes—hermeneutic, semic, symbolic, proairetic, and gnomic (cultural)—as representations of plastic waste issues and the environmental crisis in Indonesia. A qualitative research design with a content analysis approach was employed. Data were collected through in-depth observation of ten selected scenes, which were subsequently analyzed based on the five semiotic codes. The findings indicate that the symbolic code is the most dominant in conveying hidden meanings, particularly through visual elements such as plastic packaging, drinking bottles, landfill settings, and changes in the main character’s facial expressions. These symbolic elements construct both denotative and connotative meanings related to the harmful impacts of plastic waste on the environment and human life. In contrast, the gnomic code appears least frequently, primarily through the use of the text “Mother Earth” and the character’s vocal intonation, reflecting cultural values and collective environmental awareness. The proairetic code plays a significant role in presenting sequences of concrete actions addressing plastic waste management, while the hermeneutic code creates elements of enigma that encourage audiences to actively interpret the film’s environmental messages. This study concludes that nonverbal communication in Irony Mother Earth Calling effectively conveys hidden meanings through the application of Roland Barthes’ semiotic codes, positioning the film not only as a medium of visual expression but also as an educational tool for fostering environmental awareness and human responsibility toward ecological sustainability.